Kajian Hermeneutika dalam Sjair Iblis - Fajar Hardi Muhammad; Jefrizal Jefrizal (Manuskripta, 2019)
Abstract: Sjair Iblis is one of the manuscripts which is a religious group containing the teachings and beliefs of Muslims. Poetry of the Devil is included in one of the manuscripts that the author and the author do not know about, or better known as "Anonymous". The original Devil Poetry text is still stored well at the University of Leiden Netherlands with KITLV 219. However, the code is not found in any catalog such as the catalog of Maleische Handschriften Musem van het Bataviaasch Genootschap van Kunsten en Wefenschappen dan catalogus of Malay, Minangkabau and South Sumatran Manuscripts In The Netherlands, even that catalog was not identified KITLV 219 code. This study refers to the study of HG Gadamer hermeneutics using descriptive qualitative methods. Interestingly this Devil Poetry script because there are several things to be analyzed with the concept of Gadamer hermeneutics, this study also aims at how to find out the interpretation of the text of the Devil Poetry itself then this study provides treasures in the fields of religion, communication, language and understanding to the relationship between the past and the present. --- Abstrak: Syair Iblis salah satu naskah yang merupakan golongan keagamaan berisi tentang ajaran serta kepercayaan umat Islam. Syair Iblis termasuk dari salah satu naskah yang tidak diketahui pengarang dan penulisnya, atau yang lebih dikenal dengan sebutan “Anonymous”. Naskah Syair Iblis yang asli masih tersimpan baik di Universitas Leiden Netherlands dengan kode KITLV 219. Akan tetapi kode tersebut tidak ditemukan pada katalog manapun seperti katalogus Maleische Handschriften Musem van het Bataviaasch Genootschap van Kunsten en Wefenschappen dan catalogus of Malay, Minangkabau and South Sumatran Manuscripts In The Netherlands, katalog itupun tidak teridentifikasi kode KITLV 219. Penelitian ini mengacu kepada kajian hermeneutika H.G Gadamer dengan metode kualitatif deskriptif. Menariknya naskah Syair Iblis ini karena ada beberapa perihal untuk dapat di analisis dengan konsep hermeneutika Gadamer, Penelitian ini juga bertujuan bagaimana mengetahui interpretasi teks terhadap Syair Iblis itu sendiri kemudian penelitian ini memberikan khazanah dalam bidang keagamaan, pernaskahan, bahasa dan pemahaman hingga hubungan antara masa lalu dan masa kini.